2001
DOI: 10.1097/00004647-200111000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Sodium Orthovanadate on Delayed Neuronal Death after Transient Forebrain Ischemia in Gerbil Hippocampus

Abstract: In transient forebrain ischemia, sodium orthovanadate as well as insulinlike growth factor-1 (IGF-1) rescued cells from delayed neuronal death in the hippocampal CA1 region. Adult Mongolian gerbils were subjected to 5-minute forebrain ischemia. Immunoblotting analysis with anti-phospho-Akt/PKB (Akt) antibody showed that phosphorylation of Akt at serine-473 (Akt-Ser-473) in the CA1 region decreased immediately after reperfusion, and in turn transiently increased 6 hours after reperfusion. The decreased phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 89 publications
5
69
2
Order By: Relevance
“…[47][48][49][50] Interestingly, recent studies have shown that OV treatment rescues neuronal death of the gerbil and rat hippocampus after transient ischemia via PI3K/ Akt and MAPK pathways. 51,52 It has also been reported that OV protects cardiomyocytes from ischemia-reperfusion injury in the rat heart through Akt activation. 53 Our data are consistent with a recent report demonstrating that adenoviral gene transfer of the constitutively active form of Akt protects the rat liver from ischemia-reperfusion injury with increased phosphorylation of Bad at Ser-136.…”
Section: Discussionmentioning
confidence: 96%
“…[47][48][49][50] Interestingly, recent studies have shown that OV treatment rescues neuronal death of the gerbil and rat hippocampus after transient ischemia via PI3K/ Akt and MAPK pathways. 51,52 It has also been reported that OV protects cardiomyocytes from ischemia-reperfusion injury in the rat heart through Akt activation. 53 Our data are consistent with a recent report demonstrating that adenoviral gene transfer of the constitutively active form of Akt protects the rat liver from ischemia-reperfusion injury with increased phosphorylation of Bad at Ser-136.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, both Fas ligand and Bim are induced in the ventricular cardiomyocyte after myocardial ischemia/reperfusion-induced injury (18,30). Moreover, we previously documented the FOXOs-mediated increased expression of Fas ligand and Bim in ischemic brain injury in a mouse bilateral common carotid artery occlusion model (61,62,66,67). VO(OPT) treatments prevented ischemia/reperfusion injury-induced expression of Fas ligand and Bim in rat heart (18,19) and brain (51).…”
Section: +mentioning
confidence: 92%
“…These antibodies have been reported to cross-react with Mongolian gerbils. [16][17][18][19][20] Cytoplasmic extract (10 µg per sample) obtained during the preparation of nuclear extracts was fractionated by SDS-PAGE and electrophoretically transferred to a polyvinylidene difluoride membrane. Detection was performed using ECL reagents (Amersham Life Science, Arlington Heights, IL).…”
Section: Immunoblot Analysis Of Mitogen-activated Protein Kinases Andmentioning
confidence: 99%